Customer Relationship Management (CRM) Dimensions on Hotel Customer Satisfaction - Nurul Hafizah Mohd Fauzi; Siti Aisyah Mustafa (Research in Management of Technology and Business, 2024)
This study examines the impact of Customer Relationship Management (CRM) on customer satisfaction in the hotel industry in Johor Bharu, Malaysia. It examines CRM dimensions such as Customer Orientation, CRM Organisation, CRM-based Technology, and Knowledge Management. The research uses a correlational quantitative cross-sectional survey approach and a sample size of 200 customers. The findings provide insights for marketing, hotel management, and consumer relationship studies, enabling informed decisions on resource allocation, training programs, and technology investments.